Deixis Found in Kobe Bryant Interview Entitled “Love What You Do” - Rizki Arianto; Putu Nur Ayomi (CV Wahana Publikasi, 2023)
The aim of this research is to determine the deixis varieties employed in Kobe Bryant’s interview. This research employed a descriptive qualitative research design and used theory proposed by Yule (1996). The data source was a video taken from a YouTube channel, English Speech, entitled Kobe Bryant: love what you do. The findings indicate that three different kinds of deixis were used in the Kobe Bryant interview: persoaln, spatial, and temporal deixis. Personal deixis is the predominant deixis discovered in Kobe Bryant interview because, when Kobe Bryant recounted his struggles and experiences of becoming one of the best basketball players in the world, he used the words “I” and “you” a lot.